A call from justice to support the people in Gaza. Issue 2 (17th April 2019) - Lederman, Zohar; Lederman, Shmuel; Daniels, Emily Shepp
Abstract: Using Madison Powers and Ruth Faden's definition of 'well‐being, ' the authors argue that Israel, the international community and public health practitioners have a justice‐based obligation to assist the Palestinian people in the Occupied Palestinian Territories. Focusing on Palestinians in Gaza, the authors first outline a normative framework of justice, as articulated by Powers and Faden. Following Powers and Faden's assumption that empirical assessments of justice can be made using the six dimensions of well‐being, the authors next present current data on the living conditions in Gaza and describe how these conditions prevent residents from achieving sufficient levels of well‐being. Using these indicators to demonstrate that Palestinians living in Gaza suffer deficiencies in these dimensions of well‐being, the authors present a strong argument from justice to assist the residents of Gaza. The medical, public health, and bioethics community cannot sit idle while injustice continues.